A Pairwise Test Suite Generator based on Melody Search Algorithm - Toh, S. Yuen; Al-Omoush, Ala’a A.; Foo, W. Wen; Goh, G. Hau; Alsewari, Abdulrahman A. (MedWellmyJournal, 2016)
Abstract. Melody Search Algorithm (MS) has been adopted to solve many optimization problems such as combinatorial testing. This paper aims to introduce MS as a pairwise testing strategy called a Pairwise Test suite generator based Melody Search Algorithm (PTMS). A pairwise testing is an operative approach in the combinatorial test suite construction. It will minimize the constructed test suite size to save the testing time with effective defects being detected. The proposed strategy generates the test suite with real-valued variables. A comparative evaluation revealed that the PTMS is efficient in constructing a minimum test suite with the existing strategies.